Characteristics of phases and processing techniques of high entropy alloys - Chika Oliver Ujah; Daramy Vandi Von Kallon (International Journal of Lightweight Materials and Manufacture, 2024)
Production techniques used in processing alloy and composite materials have the propensity of improving their properties or deteriorating them. Therefore, appropriate choice of processing routes is a prerequisite for the development of top-notch high entropy alloys (HEAs). The types and forms of phase(s) developed in HEAs are also influenced by the processing technique. Incidentally, their properties are influenced by the phases present. So, the aim of this study was to investigate the characteristics of phases present in HEAs, and how they affect their properties and applications. More so, to investigate the processing techniques used in the development of HEAs and their influence on their properties and applications. The resource materials were sourced from Scopus database and google scholar website of articles published in the last ten years, laying more emphasis on the most recently published works. In the study, it was discovered that formation of the phases was dependent on: was dependent on: the type of the production process, present elements and the employed processing parameters. Hence, it was concluded that optimization of processing parameters and careful selection of elements are the key factors to develop HEAs of reputable properties.